Historical Aspects Of The Development Of International Relations In Uzbekistan (Zien Journal of Social Sciences and Humanities, 2023)
This article highlights the influence of inter-ethnic relations, which have historically been formed on the territory of Uzbekistan, on national culture. Also, the specific features of inter-ethnic relations are revealed. At the same time, the traditions of tolerance and their specific formation factors, which are the basis for the formation of national cultural processes in the territory of Uzbekistan, have been scientifically analyzed.